Narrations contained in the book of the meanings of the Qur’an for Al-Farra, (207H) From Surat Al-Hashr to the end of the book - Collect and study - - Qais Taha Yassin Zahoo; Adeeb Mohammed Hassana (Islamic Sciences Journal, 2024)
ABSTRACT Praise be to God, Lord of the worlds, and prayers and peace be upon the faithful Prophet who was sent as a mercy to the worlds, and upon his family and all his companions, and upon those who are guided by their gift until the Day of Judgment. As for after: This research came under the title (The narrations contained in the book “The Meanings of the Qur’an” by Al-Farra from Surat Al-Hashr to the end of the book - a collection and a study -) in order to deal with the most important narrations mentioned by Imam Al-Farra’ - may God have mercy on him - in the folds of his book The Meanings of the Qur’an regarding the interpretation of the Qur’anic verses from clarifying the meaning, Or a statement of a ruling, or the reason for the revelation, and the structure of the research consisted of: an introduction, two chapters, and its conclusion: the first chapter included the definition of Imam Al-Farra - may God have mercy on him - and mentioned his personal and scholarly biography, and the definition of his book (The Meanings of the Qur’an), while the second chapter dealt with the narrations contained in Surat Al-Hashr . Then the letter concluded with a set of results.